Socio-Economic Determinants of Student Mobility and Inequality of Access to Higher Education in Italy - Turk, Umut (Springer, 2019)
This paper introduces a modified version of the Hansen-gravity model as a framework to estimate the accessibility of higher education (HE) institutions in Italy from equal opportunities perspective. The fundamental assumption underlying gravity models is that accessibility decreases with spatial distance from opportunities. The paper extends the gravity equation to include socio-economic factors influencing the access to HE. The findings reveal differences in response to quality and other institutional characteristics by parental background and gender. Finally, decomposition of overall inequality into spatial and aspatial components reveals both the physical and social distance between groups of students seeking higher education opportunities in the country.
Turk, Umut/0000-0002-8440-7048;
Keywords: Spatial Interaction; Higher Education Accessibility; Gravity Model; Equality of Opportunity